The SwiftScan step-and-shoot continuous mode improves SPECT scanning efficiency: a preliminary phantom and clinical test - Jicheng Li; Kai Zhang; Xingru Pang; Lele Huang; Xiaoxue Tian; Jiangyan Liu (EJNMMI Physics)
Abstract Purpose The aim of the study was to investigate the value of SwiftScan Step-and-Shoot Continuous (SSC) scanning mode in enhancing image quality and to explore appropriate scanning parameters for reducing scan time. Methods This study was composed of a phantom study and two clinical tests. The differences in visual image quality scores, coefficient of variance (COV) of the background, image signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR), and recovery coefficient (RC) of the sphere were compared between SSC mode and traditional Step-and-Shoot (SS) mode in the phantom study. Various “shoot” acquisition times (5s, 10s, 15s) and “step” angles (3-degree, 6-degree, 9-degree) were evaluated and verified. In the clinical tests, bone tomography and parathyroid tomography were performed on 30 patients each. Differences in visual image quality scores, background COV, image SNR, CNR, and standardized uptake value (SUV) of lesions were compared between the two modes. Results In the phantom study, SSC mode demonstrated higher visual scores and significantly reduced background COV (P < 0.05), and significantly increased SNR and CNR (P < 0.05) compared to SS mode. No significant alteration in RC was observed (P > 0.05). In the clinical tests, no significant differences were found between the optimal SSC scan combination (10s “shoot” and 6-degree “step”)/ (10s “shoot” and 3-degree “step”) and the traditional SS scan combination (15s “shoot” and 6-degree “step”)/ (15s “shoot” and 3-degree “step”) in visual image quality scores, background COV, image SNR, CNR, and SUV of bone and parathyroid high uptake lesions (P > 0.05). Conclusion The SwiftScan SSC mode can reduce acquisition time by 33% while maintaining similar image quality and quantification accuracy compared to SS mode. An SSC scanning protocol with a 10s “shoot” acquisition and 6-degree “step” or with a 10s “shoot” acquisition and 3-degree “step” over a 360-degree rotation, is recommended for clinical use.